CONCEPT OF OVERALL THERMAL TRANSFER VALUE (OTTV) IN DESIGN OF BUILDING ENVELOPE TO ACHIEVE ENERGY EFFICIENCY - CHINMAYA BISWAL,DHANUNJAYA NAIK MUDE,KUMMARI UPENDER, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Design of energy efficient buildings is the quickest way to reduce energy consumption. The skin of the building acts as a barrier between the indoor environment and the outdoor environment. The thermal performance of a building depends upon the façade design to a large extent, ranking second to the local climatic characteristics. Potential for energy conservation exists in all building typologies, but it becomes more of a concern in energy intensive buildings such as air-conditioned offices and shopping malls. This paper discusses the significance of the Overall Thermal Transfer Value (OTTV) controls as a means of enhancing energy efficiency of buildings. OTTV is a measure of heat gain into the building through the building envelope. It also acts as an index for comparing the thermal performance of buildings. The objectives and need for OTTV controls are discussed. The parameters used in calculating OTTV and therefore the need to customize OTTV calculations based on the location of the building are analyzed. The paper also discusses the OTTV standards in countries such as Singapore, Malaysia, Jamaica and Thailand. The application and calculation of OTTV for a case study building is demonstrated. The paper discusses the limitations of OTTV standards, its significance and relevance, and concludes that OTTV is one of the means of achieving energy efficiency of air conditioned buildings.